Sustainability of the Communities That Care Prevention System by Coalitions Participating in the Community Youth Development Study - Gloppen, Kari M. (2012)
PURPOSE: Community prevention coalitions are a common strategy to mobilize stakeholders to implement tested and effective prevention programs to promote adolescent health and well-being. This paper examines the sustainability of Communities That Care (CTC) coalitions approximately 20 months after study support for the intervention ended. METHODS: The Community Youth Development Study (CYDS) is a community-randomized trial of the CTC prevention system. Using data from 2007 and 2009 coalition leader interviews, this study reports changes in coalition activities from a period of study support for CTC (2007) to 20 months following the end of study support for CTC (2009), measured by the extent to which coalitions continued to meet specific benchmarks. RESULTS: Twenty months after study support for CTC implementation ended, 11 of 12 CTC coalitions in the CYDS still existed. The 11 remaining coalitions continued to report significantly higher scores on the benchmarks of phases 2 through 5 of the CTC system than did prevention coalitions in the control communities. At the 20-month follow-up, two-thirds of the CTC coalitions reported having a paid staff person. CONCLUSIONS: This study found that the CTC coalitions maintained a relatively high level of implementation fidelity to the CTC system 20 months after the study support for the intervention ended. However, the downward trend in some of the measured benchmarks indicates that continued high-quality training and technical assistance may be important to ensure that CTC coalitions maintain a science-based approach to prevention, and continue to achieve public health impacts on adolescent health and behavior outcomes.